High-speed observations of football-boot-surface interactions of players in their natural environment - Kirk, R. F.; Noble, I. S. G.; Mitchell, T.; Rolf, C.; Haake, S. J.; Carre, M. J. (Sports Engineering, 2007)
A protocol has been developed to obtain two-dimensional kinematic shoe data of football players in their training environment through high-speed video analysis. Such kinematic data can provide an understanding of how to better replicate the boundary conditions of football movements when simulated using mechanical traction and penetration test devices. As part of a pilot study, 11 youth academy players from a Premiership football club performed football-specific movements which were filmed at 1000 frames s-1. The protocol required minimal set-up time and the area of the pitch to be filmed could be positioned in any part of the playing area, causing low disruption to the players. This aimed to ensure that the movements performed were representative of those carried out during competitive play. Results in this study are concerned with the kinematics of the shoe during contact with the ground for movements identified to be important in terms of injury risk and loss of performance (slipping). Shoe velocities and orientations were measured for subjects wearing shoes of different stud types (traditional round studs versus contemporary bladed studs) on two surfaces (artificial turf, in-filled with rubber and sand, versus a natural surface). All the parameters measured from the relatively small population of subjects had high variances and therefore few significant effects of studs and surface could be found. The data does however provide insight into the appropriate boundary conditions to be used in mechanical test devices. For example, in the forefoot push-off movement it can be seen that test devices should measure the traction forces when the shoe first starts to move, as this is when the player would lose performance, as opposed to the maximum traction which can occur after significant displacement of the shoe through the surface. Analysis of the orientation and velocity path of the studs just before contact with the ground shows that the studs could be aligned to enhance their penetration into the surface and optimise the traction properties of the studs. In order to determine the orientation and velocity of the shoes at crucial phases in movements force-plate data obtained in the laboratory should be utilised in future studies.